Reversible thyrotoxicosis caused by suppurative thyroiditis in a young healthy woman - Begüm Süeda Sert; Roderick F.A. Tummers-de Lind van Wijngaarden; Jacqueline Buijs (European Journal of Case Reports in Internal Medicine)
Introduction: Acute suppurative thyroiditis is a bacterial infection of the thyroid gland. Potential risk factors are an immunocompromised state or the presence of pre-existing thyroid disease. Acute suppurative thyroiditis may be complicated by abscess formation and/or thyrotoxicosis, which are both rare but potentially life-threatening complications. Case description: We describe a case of acute suppurative thyroiditis secondary to tonsillitis in a 22-year-old healthy female presenting with thyrotoxicosis due to abscess formation. She presented with complaints of palpitations, fever, extreme salivation, dysphagia, pain and swelling of the neck. Further analysis revealed a sinus tachycardia, high inflammatory parameters, and clinical and biochemical signs of thyrotoxicosis. Computed tomography showed abscess formation in the left lobe of the thyroid gland with extension to the retropharyngeal space and deviation of the trachea to the contralateral side. Blood cultures were positive for Streptococcus constellatus and Prevotella intermedia. The patient was treated with antibiotics and underwent an operative excision and drainage of the abscess and recovered well. Symptomatic thyrotoxicosis was treated with metoprolol. P. intermedia has not previously been implicated in causing acute bacterial thyroiditis. Conclusion: Acute suppurative thyroiditis may occur in healthy young adults without any predisposing factors. Concomitant thyrotoxicosis is rare, but important to diagnose. Bacterial thyroiditis may be either a primary thyroid infection or a secondary complication of a severe tonsillitis. Early recognition and treatment are of great importance to reduce overall mortality and morbidity, and to prevent the development of complications.